LIVING HADIS: KONTRUKSI SOSIAL NILAI-NILAI TAHÄ€DÅª TAHÄ€BÅª DALAM TRADISI TONGEBAN - Moh. Jufriyadi Sholeh (Al-Amien Prenduan University, Sumenep, 2023)
Cultural values and traditions in Muslim society cannot be separated from the values of the teachings of the Koran and the hadith of the Prophet. Every local culture and custom that exists during their lives will continue to be maintained with legality expressed or implied in the instructions of the Al-Qur'an and Hadith. The tongeban tradition among Madurese Muslims, which was built in the spirit of returning the visit of the male in-law's family by bringing a cake, is part of the living hadith in the form of implementing the values of the Prophet's hadith